Cremation and the 'ethical' handling of ashes - Alfano, linda; Malcotti, Ivano; Ciliberti, Rosagemma (Medicina Historica, 2023)
Several new alternatives to traditional burial have emerged through the years, including the communal cinerary urn option which involves the cremation of the deceased and the burial of their ashes in a shared burial, often located in a dedicated site, such as a memorial garden or a cemetery.Understanding the motivations and ethical considerations, that guide people's burial choices can offer valuable insights for both practitioners and those who are faced with making decisions regarding their own burial, or that of their loved ones. This study aims to examine funeral rites and the concept of the communal cinerary urn exploring, through interviews conducted with family members of people who have chosen this option, the personal, cultural, economic, and spiritual motivations that led them to opt for this form of burial, while also analysing the ethical concerns and emotions associated with this choice, including feelings of loss, respect, and remembrance.